2014
DOI: 10.1080/10401334.2014.883981
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Patient Assessments as a Medical Student: Frequency, Barriers, and Facilitators

Abstract: Our study demonstrated variation in the frequency of patient assessments, and weak relationships between numbers of assessments, student confidence, and barriers to seeing patients. Further investigation is warranted of the impact of fewer opportunities for deliberate practice of skills for expertise development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a closed-question survey of 241 MMS students in 2011, 19% reported that they 'lacked the confidence to approach patients' and 11% reported having 'assessed fewer than six patients in each of their rotations'. 20 We asked the following research question: What are the individual and environmental factors affecting medical students' unsupervised encounters with hospital patients? METHODS We adopted an ethnographic approach to the research: extended field observations allowed the researcher (JB) to enter the clinical learning world of the students 21 and semi-structured interviews allowed her to sample students' views of their experiences (Appendix S1, online).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a closed-question survey of 241 MMS students in 2011, 19% reported that they 'lacked the confidence to approach patients' and 11% reported having 'assessed fewer than six patients in each of their rotations'. 20 We asked the following research question: What are the individual and environmental factors affecting medical students' unsupervised encounters with hospital patients? METHODS We adopted an ethnographic approach to the research: extended field observations allowed the researcher (JB) to enter the clinical learning world of the students 21 and semi-structured interviews allowed her to sample students' views of their experiences (Appendix S1, online).…”
Section: Resultsmentioning
confidence: 99%
“…In considering the ‘black box’ of clinical learning, we responded to local concerns about whether students see enough patients in their clerkships, particularly during their self‐directed learning time when they are not directly supervised by a member of the medical team. In a closed‐question survey of 241 MMS students in 2011, 19% reported that they ‘lacked the confidence to approach patients’ and 11% reported having ‘assessed fewer than six patients in each of their rotations’ . We asked the following research question: What are the individual and environmental factors affecting medical students' unsupervised encounters with hospital patients?…”
Section: Introductionmentioning
confidence: 99%